The conservation management for heritage traditional buildings in Malaysia / Nor Azelina Hanum Ahmad Rafid - Ahmad Rafid, Nor Azelina Hanum (Faculty of Architecture, Planning and Surveying, 2015)
This study was conducted to describe the management of conservation of traditional heritage buildings in Malaysia. The conservation refer to all the processes of looking after a place so as to retain its historical and architectural, aesthetic, cultural significance and includes maintainance, preservation, restoration, reconstruction and adoption or a combination of more than one of these. The aim in this research is to study current issues and problems relating to the conservation management for heritage traditional buildings that has Malay identity in every country use different approaches or practise guideline to expand knowledge about the conservation of heritage buildings to the community. The objectives of this reseacrh can identified; to study the scenario of conservation management on traditional heritage buildings, to identifiy the problem that occurs is the management of buildings conservation awareness and lastly, to recommend good conservation management practices for traditional heritage buildings in Malaysia. Several method are use to conduct the analysis, that are the interview and observation. The interview from expert parties in conservation scope and the observation done by to look and identify the structure and design of heritage buildings. Based on the analysis, researcher found that heritage traditional buildings is well maintain and manage on their structure on buildings. The structure buildings is good maintenance by Department of National Heritage.